(untitled) (Research, Society and Development, 2021)
COVID-19 is an infectious disease caused by the new coronavirus (SARS-CoV-2). With the arrival of the new coranavirus pandemic, healthcare professionals became directly involved in the frontlines of the care, diagnosis and treatment of patients with COVID-19. The aim of this study was to analyze the challenges faced by pharmacists in assisting and combating SARS-CoV-2 infection in times of pandemic. An Integrative Literature Review was carried out, observational, descriptive in nature, with a qualitative approach, allowing the association of clinical evidence to the practice of professionals working in the health area, in relation to research and health care. Searches were carried out in the Virtual Health Library, Google Scholar, SciELO, Latin American and Caribbean Literature in Health Sciences databases in the period 2020 – 2021, in Portuguese and English on the subject. The search identified a total of 32 articles, of which 14 met the selection criteria. The results showed that pharmaceutical assistance is responsible for providing medication to the population, considering the principles of safety and efficacy, and always having rational use as the objective of its activities. However, a significant increase in the demand for self-medication drugs is evident, which ends up putting the population’s health at risk, thus, there is a need to improve strategies aimed at patient safety. Research is still ongoing and new results will emerge, so future studies are recommended for further research on this topic.